2022
DOI: 10.1111/jce.15524
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in coronary venous drainage: Challenges and solutions in delivering cardiac resynchronization therapy

Abstract: Aims To investigate the abnormalities of the coronary venous system in candidates for cardiac resynchronization therapy (CRT) and describe methods for circumventing the resulting difficulties. Methods From four implanting institutes, data of all CRT implants between October 2008 and October 2020 were screened for abnormal cardiac venous anatomy, defined as an anatomical variation not conforming to the accepted ‘normal’ anatomy. Patient demographics, procedural detail, and subsequent left ventricle (LV) lead pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The femoral vein provides large, linear, direct access to the heart via the inferior vena cava and, therefore, has been used to overcome the challenging angulations associated with the subclavian access. 32 The large bore access permits the use of sizable snares safely, and the direct pathway to the heart chambers provides a geometric advantage during application of extraction forces. In a small observational study, the use of femoral snare lead extraction was found to be a successful bail-out strategy; the overall rate of clinical success and complete lead extraction was improved with the addition of femoral snare extraction after the subclavian approach had failed; without this strategy, the procedural success would have been lower than contemporary expectations.…”
Section: Rotational Sheathmentioning
confidence: 99%
“…The femoral vein provides large, linear, direct access to the heart via the inferior vena cava and, therefore, has been used to overcome the challenging angulations associated with the subclavian access. 32 The large bore access permits the use of sizable snares safely, and the direct pathway to the heart chambers provides a geometric advantage during application of extraction forces. In a small observational study, the use of femoral snare lead extraction was found to be a successful bail-out strategy; the overall rate of clinical success and complete lead extraction was improved with the addition of femoral snare extraction after the subclavian approach had failed; without this strategy, the procedural success would have been lower than contemporary expectations.…”
Section: Rotational Sheathmentioning
confidence: 99%
“…There are various approaches that have been described in the literature to overcome the difficulties encountered during the placement of CS lead in a patient with PLSVC. 6 Some operators opt for implantation of the entire system via the right subclavian approach, while others implant only the LV lead via the right subclavian approach and then tunnel the lead to a left pre-pectoral pocket. Access to the CS from the RA may sometimes be challenging due to ostial stenosis, unroofed CS, and variable connections with the smooth part of the RA.…”
Section: Strategies For Device Implantation In Patients With Plsvcmentioning
confidence: 99%
“…Access to the CS from the RA may sometimes be challenging due to ostial stenosis, unroofed CS, and variable connections with the smooth part of the RA. 6 Access to the CS in these situations may be facilitated by using an Amplatz Left 2 coronary catheter (Merit Medical) with a secondary curve to access the CS. In rare situations, tight angulation of the CS ostium can be navigated using 0.014-in guidewire via the PLSVC to the RA, where it can be snared from the femoral access for railroading the guide sheath into the CS to deliver the LV lead.…”
Section: Strategies For Device Implantation In Patients With Plsvcmentioning
confidence: 99%
“…4,9 This is unfavourable compared with conventional CRT systems, which can be successfully implanted in up to 97-99% of cases (in experienced hands) on the first attempt, and in >99% of cases using unconventional methodologies with repeat procedures. [10][11][12] The CRT implantation failure rate is extremely low.…”
Section: Leadless Crtmentioning
confidence: 99%